Lifelong pulmonary sequelae of bronchopulmonary dysplasia. Issue 2 (April 2020) - Sillers, Laura; Alexiou, Stamatia; Jensen, Erik A.
Abstract : Purpose of review: To summarize the current literature evaluating long-term pulmonary morbidity among surviving very preterm infants with bronchopulmonary dysplasia (BPD). Recent findings: BPD predisposes very preterm infants to adverse respiratory signs and symptoms, greater respiratory medication use, and more frequent need for rehospitalization throughout early childhood. Reassuringly, studies also indicate that older children and adolescents with BPD experience, on average, similar functional status and quality of life when compared to former very preterm infants without BPD. However, measured deficits in pulmonary function may persist in those with BPD and indicate an increased susceptibility to early-onset chronic obstructive pulmonary disease during adulthood. Moreover, subtle differences in exercise tolerance and activity may put survivors with BPD at further risk of future morbidity in later life. Summary: Despite advances in neonatal respiratory care, a diagnosis of BPD continues to be associated with significant pulmonary morbidity over the first two decades of life. Long-term longitudinal studies are needed to determine if recent survivors of BPD will also be at increased risk of debilitating pulmonary disease in adulthood.